Chapter A Student Voice Approach in Work-Related Learning. From Lesson-Learned in Secondary School to Suggestions for Higher Education - Esposito, Gilda (Studies on Adult Learning and Education, 2018)
This paper presents a research on work-related learning through School-work Alternance in Secondary Education that involved researchers of University of Florence, ten secondary Schools, public and private entities in the Province of Arezzo and La Spezia. From the analysis of three case studies, it elicits criteria for an educational model that integrates work-related learning with student voice perspective